Pengembangan Perangkat Lunak IoT Cloud Platform Berbasis Protokol Komunikasi HTTP - Ocki Bagus Pratama; Adhitya Bhawiyuga; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The primary aim of Internet of Things (IoT) is to expand the benefits of Internet connectivity by connecting objects around us to the internet, thus enabling remote control and accessibility. IoT devices often have limitations in terms of storage capacity and computing capabilities. This requires the IoT device to be integrated with systems that have better computing capabilities One of them is cloud-based computing system. However, the integration between IoT and cloud devices has challenges in terms of network communication, security, and device management. Network communication is the number of network technologies being used, thus the selection of communication protocols should consider its support for a variety of devices. Security and privacy are a concern because of the large number of IoT devices that can be easily connect to the cloud, requiring authentication and authorization that is required to identify and validate devices that transmit the data. Device management is required due to the large number of IoT devices that will be used, it requires a device management mechanism. Based on those problems, a solution was proposed on IoT cloud platform design using HTTP communication protocol to solve network communication and RESTful for device management constraints. As for identifying and validating devices that transmit data, an authentication and authorization mechanism using JSON Web Token is utilized. The result of system performance testing, is that the built systems are capable of handling up to 100 users simultaneously.